PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN ARTICULATE STORYLINE 3 BERBASIS MASALAH UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI PENGUMPULAN DAN PENYAJIAN DATA DI KELAS V SD - Sri Rahayu Murwaningsih; Sukmawarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is very important for humans in all aspects of their lives. Learning is an effort made deliberately by educators to convey knowledge, organize and create environmental systems using various methods so that students can carry out learning activities effectively and efficiently with optimal results. However, in reality, based on observations carried out by researchers at UPTD SDN 010131 Pulau Rakyat Tua, students in class V think that mathematics is difficult, teachers still use print media in learning, then the level of student concentration in learning is low, and students pay less attention to the teacher during the learning process. . Given the problems above, efforts need to be made to overcome them. The researcher developed different variations of technology-based learning media, namely Interactive Learning Media Assisted by Articulate Storyline 3. This research aims to determine student responses, determine the validity, practicality, effectiveness of the development of problem-based interactive learning media assisted by Articulate Storyline 3 to increase understanding of concepts in the collection material. and presenting data in class V at UPTD SDN 010131 Pulau Rakyat Tua. This research method uses research and development (R&D) with the ADDIE development model. Data on the level of suitability of the media Interactive Learning Media Assisted by Articulate Storyline 3can be measured from the level of students' mastery of the material being taught with the results known as student responses based on the questionnaire given to all students, 29 students obtained a percentage of 81%. The results of the teacher's response to the media developed obtained a percentage of 94%. The validation results in the media study developed obtained a percentage of 83%. The validation results in the study of the material contained in the media developed obtained a percentage of 85%. From the results above, the media developed has been declared very feasible or very valid. Keywords: Education, Interactive Learning Media, Articulate storyline 3